INTERFAITH DIALOGUE AS THE BASIS FOR INCLUSIVE RELIGIOUS POLICY: REINTERPRETING THE THOUGHT OF A. MUKTI ALI IN THE CONTEXT OF INDONESIAN PLURALISM - Yohanes, Santo (Journal of Religious Policy, 2025)
This study examines interfaith dialogue as the basis for the formation of inclusive religious policies through a reinterpretation of A. Mukti Ali's thinking in the context of Indonesian pluralism. The focus of the study is on how Mukti Ali's ideas on dialogue can be translated into principles of religious governance that uphold citizen equality, respect for diversity, and the strengthening of social cohesion. This study uses a qualitative approach based on literature review, combining qualitative content analysis and hermeneutic interpretation to trace the works of A. Mukti Ali, both academic texts and policy documents related to his tenure as Minister of Religious Affairs, in order to critically reconstruct the paradigmatic relevance of his thinking for the development of inclusive religious policy in Indonesia. Based on the analysis, three key elements were found that make Mukti Ali's thinking significant for the formulation of Indonesia's current religious policy. First, he positioned interfaith dialogue as an operational social instrument through the strengthening of interfaith communication forums and the creation of meeting spaces to build mutual understanding. Second, he offered a concept of religious policy that rejected exclusivism by emphasizing inclusiveness as an ethical principle in state-religion relations. Third, the dialogical framework he proposed provides a practical basis for responding to polarization, intolerance, and radicalism that threaten social integration. In conclusion, this reinterpretation of Mukti Ali's thinking shows that interfaith dialogue is not merely a normative idea, but a conceptual foundation that can strengthen the direction of civilized public policy in Indonesia's multireligious society.